ANALYSIS OF EFFECT PAY EQUITY INDIRECT INCENTIVE SYSTEM TOWARD ORGANIZATIONAL COMMITMENT OF EMPLOYEES AT THE HOSPITAL IN YOGYAKARTA - Fitri, Eirna Syam; Pribadi, Firman; Astuti, Rini Juni (Archives of Business Research, 2018)
There is one of the government hospital in Yogyakarta that has been applying the remuneration system in an indirect incentives. Based on regulation in there, we can give a question of whether there is a pay equity for those who play the role. The emergence of reward inequality can affect organizational commitment, where organizational commitment greatly affects professional work situation. This research is a quantitative analytic research. The data retrieval technique uses a questionnaire containing closed questions with the choices of answers that have been scored. The sampling method is stratified random sampling. This result indicates that there is positive influence of pay equity toward organizational commitment.